2011
DOI: 10.1203/pdr.0b013e3182242461
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Diagnosis of Rett Syndrome in Australia

Abstract: Modifications to diagnostic criteria and introduction of genetic testing have likely affected the pattern and timing of Rett syndrome diagnosis. The trends in incidence and prevalence of Rett syndrome in Australia were examined; the cumulative risk of a female being diagnosed determined; and the impact of changes to diagnostic criteria and availability of genetic testing on these frequencies investigated. The population-based Australian Rett Syndrome Database was used to identify a total of 349 verified Rett s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

9
1

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 36 publications
3
98
1
1
Order By: Relevance
“…Several studies showed a mild-to-moderate increase in RTT incidence over previous decades [14,23], which was also observed in our study. Such tendency could be explained by advances in clinical and molecular diagnosis of RTT.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies showed a mild-to-moderate increase in RTT incidence over previous decades [14,23], which was also observed in our study. Such tendency could be explained by advances in clinical and molecular diagnosis of RTT.…”
Section: Discussionsupporting
confidence: 90%
“…206 Further studies in 2011 demonstrated that the cumulative incidence was increasing with age and that the median age at diagnosis had fallen from 4.5 before to 3.5 years after 1999. 207 …”
Section: Global Efforts To Study a Rare Disorder Epidemiologymentioning
confidence: 99%
“…Combining data collected as part of InterRett, 11 an international Rett syndrome phenotype database, with data from the Australian Rett Syndrome Database (ARSD), 12 a population-based cohort, the phenotype associated with a large deletion is described in detail and compared with the phenotype of cases with other common mutations.…”
Section: Introductionmentioning
confidence: 99%